A critical review of state‐of‐the‐art chatbot designs and applications. (25th October 2021) - Luo, Bei; Lau, Raymond Y. K.; Li, Chunping; Si, Yain‐Whar
Abstract: Chatbots are intelligent conversational agents that can interact with users through natural languages. As chatbots can perform a variety of tasks, many companies have committed numerous resources to develop and deploy chatbots to enhance various business processes. However, we lack an up‐to‐date critical review that thoroughly examines both state‐of‐the‐art technologies and innovative applications of chatbots. In this review, we not only critically analyze the various computational approaches used to develop state‐of‐the‐art chatbots, but also thoroughly review the usability and applications of chatbots for various business sectors. We also identify gaps in chatbot‐related studies and propose new research directions to address the shortcomings of existing studies and applications. Our review advances both academic research and practical business applications of state‐of‐the‐art chatbots. We provide guidance for practitioners to fully realize the business value of chatbots and assist in making sensible decisions related to the development and deployment of chatbots in various business contexts. Researchers interested in the design and development of chatbots can also gain useful insights from our critical review and identify fruitful research topics and future research directions based on the research gaps discussed herein. This article is categorized under: Technologies > Machine Learning Application Areas > Business and Industry Abstract : Overview and discussion of the state‐of‐the‐art chatbot technologies and applications. AIML, artificial intelligence mark‐up language; DPO, dialogue policy optimization; DST, dialogue state tracking; GRU, gated recurrent unit; LSTM, long short‐term memory; RL, reinforcement learning; RNN, recurrent neural network; SLU, spoken language understanding.